تطوير نموذج ميكانيكي لتحليل الوصلات الفولاذية جائز-عمود المنفذة بالبراغي وصفائح جبهية غير بارزة أثناء الانهيار التدرجي - حيدر, بادية; لوحو, غاندي; الحج, خضر يوسف (Latakia University Journal -Engineering Sciences Series, 2019)
Bolted beam-to-column joints are an essential element in the performance of steel structures under exceptional loading conditions such as explosions and vehicle collisions due to the risk of a progressive collapse. In some progressive collapse scenarios (sudden column loss), joints are subject to large axial forces and deformations caused by the catenary action that develops in the beams. These properties are not encountered for joint behavior in conventional structural design, while they are essential characteristics for any realistic representation of joint performance during progressive collapse. A mechanical model has been developed to analyze bolted flush end-plate beam-to-column joints during progressive collapse due to column loss using ABAQUS. The mechanical model was validated in comparison to results obtained from published researches. The results confirmed that the developed mechanical model can simulate the main features of the response of a bolted flush end-plate beam-to-column joint under a column loss scenario with good accuracy. تشكل الوصلات جائز-عمود المنفذة بالبراغي عنصراً جوهرياً في أداء المنشآت الفولاذية تحت شروط التحميل الاستثنائية كالانفجارات واصطدام العربات بسبب خطر حدوث بالانهيار التدرجي .(progressive collapse) تخضع الوصلات في بعض سيناريوهات الانهيار التدرجي (فقدان مفاجئ لعمود ) لتشوهات وقوى محورية كبيرة ناتجة عن آلية فعل الكابل (Catenary action) التي تتطور في الجيزان، لا تصادف هذه الخصائص لسلوك الوصلة في التصميم الإنشائي التقليدي بينما تشكل خصائص جوهرية من أجل أي تمثيل واقعي لأداء الوصلة أثناء الانهيار التدرجي. تم تطوير نموذج ميكانيكي يمكن استخدامه لتحليل الوصلات جائز-عمود المنفذة بالبراغي وصفائح جبهية غير بارزة أثناء الانهيار التدرجي الناتج عن فقدان عمود باستخدام برنامج العناصر المنتهية ABAQUS. تم توثيق النموذج الميكانيكي المنجز بالمقارنة مع نتائج تجريبية مستخلصة من الأبحاث المنشورة. أكدت النتائج أن النموذج الميكانيكي المطور يستطيع وبدقة جيدة محاكاة السمات الرئيسية المميزة لاستجابة وصلة جائز-عمود منفذة بالبراغي وصفائح جبهية غير بارزة تحت سيناريو فقدان عمود.